Organizational responses to environmental demands: opening the black box - Delmas, Magali A.; Toffel, Michael W. (Strategic Management Journal, 2008)
Abstract This article combines new and old institutionalism to explain differences in organizational strategies. We propose that differences in the influence of corporate departments lead their facilities to prioritize different external pressures and thus adopt different management practices. Specifically, we argue that external constituents—including customers, regulators, legislators, local communities, and environmental activist organizations—who interact with influential corporate departments are more likely to affect facility managers' decisions. As a result, managers of facilities that are subjected to comparable institutional pressures adopt distinct sets of management practices that appease different external constituents. We test our framework in the context of the adoption of environmental management practices using an original survey and archival data obtained for nearly 500 facilities. We find support for these hypotheses. Copyright © 2008 John Wiley & Sons, Ltd.